The Effect of Solvability, Company Growth and Income Management on Going Concern Audit Opinions - Anggi Dini Puspita; Dodik Juliardi; Dhika Maha Putri (AIBPM Publisher, 2020)
This research aims to determine the influence of solvency, growth of the company, and profit management on the going concern audit opinions. The study used the analysis of the confirmatory factor to test the correlation between variables and logistical regression analyses to test the hypothesis. The selected sample in this study is a service company with the transportation sub-sector listed on the Indonesia Stock Exchange (IDX) in 2014-2018 with purposive sampling technique. The results of this study show that (1) solvency affects the going concern audit opinion, (2) The company growth does not affect the going concern audit opinion, (3) Earnings management does not affect the going concern audit opinion.